Clean Water Donations as a Strategy to Improve MSME Welfare in Aek Tuhul Village: A Qualitative Participatory Impact Assessment - Nando Farizal; Yusrizal Lubis; Ayu Hidayati; Muhammad Ariful Maarif (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyse the role of clean water donations as a strategic instrument in improving the welfare of MSMEs through production efficiency and poverty alleviation using the maqasid al-syari‘ah approach, particularly hifẓ al-nafs and hifẓ al-mal. The method used is qualitative research based on field research through in-depth interviews and focus group discussions (FGD) with 10-20 informants, which are analysed using Participatory Impact Assessment (PIA). The results show that the clean water charity model based on communal well waqf, which is built on four main pillars, can be strengthened through the use of digitalisation. Digitalisation not only serves as a means of financial recording and reporting, but is also developed in the form of a water charity distribution application that facilitates online donations, real-time monitoring of water distribution, and mapping of beneficiaries. This mechanism enhances transparency, public participation, and governance efficiency. The sustainability of the model is supported by a cross-subsidy scheme, whereby MSME contributions guarantee free access to clean water for the poor, while surplus funds are allocated for microfinance and MSME training. This research contributes to a blueprint for the development of non-APBD-based clean water infrastructure based on inclusive economics and sharia at the village level.Keywords: Clean Water Charity, Culinary Msmes, Digital Charity Application, Productive Waqf, Sharia-Based Inclusive Economy